2021
DOI: 10.3390/healthcare9060758
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ and Relatives’ Preferences for a Palliative/Oncology Day Ward and Out-of-Hours Telemedicine—An Interpretive Description

Abstract: Demographical challenges require adaptation and tailoring of services to suit palliative patients’ and relatives’ needs. Therefore, an interpretive descriptive study was performed to explore patients’ and relatives’ preferences for the establishment of a day ward and out-of-hours telemedicine. Semi-structured interviews were performed, and data were analysed using thematic analysis. Participants included patients (n = 12) and relatives (n = 5). Three themes emerged: (1) ‘Transport burden’ relates to transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…3,4,32,33,36,47,51,5759,62,63,67,70,71 Family members, where specified, were mainly patients and spouses, but also patients and; adult children, siblings, parents, friends or neighbours or other family members. 3,27,32,34,35,38,39,43,44,4649,5355,57 59,61,64,67,68,71,73 Video consultations accounted for the most frequently used technology solution, alone ( n = 11), 35,36,43,46,51,62 64,67,70,71 and in combination with other technologies; video consultations and telephone ( n = 4), 47,52,53,57 video consultations, websites and online forums ( n = 3), 38,58,59 video consultations, emails, applications (apps), and remote monitoring ( n = 2), 4,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4,32,33,36,47,51,5759,62,63,67,70,71 Family members, where specified, were mainly patients and spouses, but also patients and; adult children, siblings, parents, friends or neighbours or other family members. 3,27,32,34,35,38,39,43,44,4649,5355,57 59,61,64,67,68,71,73 Video consultations accounted for the most frequently used technology solution, alone ( n = 11), 35,36,43,46,51,62 64,67,70,71 and in combination with other technologies; video consultations and telephone ( n = 4), 47,52,53,57 video consultations, websites and online forums ( n = 3), 38,58,59 video consultations, emails, applications (apps), and remote monitoring ( n = 2), 4,…”
Section: Resultsmentioning
confidence: 99%
“…The included studies (n = 44) comprised of 19 qualitative, 3,4,27,32-47 5 quantitative [48][49][50][51][52] and 20 mixedmethods studies, spanning 18 countries in; North America, 4,[39][40][41][46][47][48]50,[53][54][55][56]58,59,[61][62][63]65,66,[68][69][70][71][72][73][74] South America, 51 Europe, 3,27,[33][34][35][36][37][38]49,52,57,60 Africa, 32,44 Asia 45,67 and Australia. 64 The palliative care context was broad including; specialised palliative care in hospital and home settings (n = 19), 3,...…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Patients and public were not actively involved in the design of this protocol. However, a motivating factor in performing this review was the findings of a qualitative study on patient and relatives’ preferences in relation to telepalliative care performed by the authors EHB and GB 40. This review protocol is part of a PhD project and will guide further coproduction studies with active patient and family participation.…”
Section: Methods and Analysismentioning
confidence: 99%
“…There is a dearth of knowledge on how telepalliative care is understood and experienced from within the family unit. Our research group has previously demonstrated how the preferences of family members influence patients’ perceptions of how they would like to receive PC in the future 40. Understanding the role that families play in telepalliative care is pivotal in understanding how or why some barriers or facilitators exist and how they present in the context of family telepalliative care.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation